KANPHOS: Kinase-associated neural phospho-signaling database for data-driven research - Kannon, Takayuki; Murashige, Satoshi; Nishioka, Tomoki; Amano, Mutsuki; Funahashi, Yasuhiro; Tsuboi, Daisuke; Yamahashi, Yukie; Nagai, Taku; Kaibuchi, Kozo; Yoshimoto, Junichiro (Frontiers in Molecular Neuroscience, 2024)
Protein phosphorylation, a key regulator of cellular processes, plays a central role in brain function and is implicated in neurological disorders. Information on protein phosphorylation is expected to be a clue for understanding various neuropsychiatric disorders and developing therapeutic strategies. Nonetheless, existing databases lack a specific focus on phosphorylation events in the brain, which are crucial for investigating the downstream pathway regulated by neurotransmitters. To overcome the gap, we have developed a web-based database named “Kinase-Associated Neural PHOspho-Signaling (KANPHOS).” This paper presents the design concept, detailed features, and a series of improvements for KANPHOS. KANPHOS is designed to support data-driven research by fulfilling three key objectives: (1) enabling the search for protein kinases and their substrates related to extracellular signals or diseases; (2) facilitating a consolidated search for information encompassing phosphorylated substrate genes, proteins, mutant mice, diseases, and more; and (3) offering integrated functionalities to support pathway and network analysis. KANPHOS is also equipped with API functionality to interact with external databases and analysis tools, enhancing its utility in data-driven investigations. Those key features represent a critical step toward unraveling the complex landscape of protein phosphorylation in the brain, with implications for elucidating the molecular mechanisms underlying neurological disorders. KANPHOS is freely accessible to all researchers at https://kanphos.jp.